2016
DOI: 10.15252/embr.201642194
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological eEF 2K activation promotes cell death and inhibits cancer progression

Abstract: Activation of the elongation factor 2 kinase (eEF2K) leads to the phosphorylation and inhibition of the elongation factor eEF2, reducing mRNA translation rates. Emerging evidence indicates that the regulation of factors involved in protein synthesis may be critical for controlling diverse biological processes including cancer progression. Here we show that inhibitors of the HIV aspartyl protease (HIV-PIs), nelfinavir in particular, trigger a robust activation of eEF2K leading to the phosphorylation of eEF2. Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
29
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 52 publications
(80 reference statements)
1
29
0
Order By: Relevance
“…Thus, the development of specific eEF2K inhibitors with improved pharmacological properties may be valuable in the fight against cancer. However, it is also important to point out that, according to some reports, knocking‐down eEF2K may actually promote tumor growth . Our data also suggest that the levels of expression of eEF2K may serve as a biological marker as to determine the cancer progression stage in patients.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Thus, the development of specific eEF2K inhibitors with improved pharmacological properties may be valuable in the fight against cancer. However, it is also important to point out that, according to some reports, knocking‐down eEF2K may actually promote tumor growth . Our data also suggest that the levels of expression of eEF2K may serve as a biological marker as to determine the cancer progression stage in patients.…”
Section: Discussionsupporting
confidence: 63%
“…However, it is also important to point out that, according to some reports, knocking-down eEF2K may actually promote tumor growth. 45,46 Our data also suggest that the levels of expression of eEF2K may serve as a biological marker as to determine the cancer progression stage in patients. Indeed, in certain types of colorectal cancer and melanoma, eEF2K expression levels are higher in normal tissues compared to the cancer ones.…”
Section: Discussionmentioning
confidence: 61%
“…While the ISR is a key response that modulates cellular homeostasis, this pathway did not affect cellular viability in presence of the HIV-PIs. In contrast, we found that NFR-mediated toxicity relied on the activation of the kinase eEF2K 2 (Fig. 1).…”
mentioning
confidence: 72%
“…Among these, we recently described that the HIV aspartyl protease inhibitors (HIV-PIs), a family of antiviral drugs, regulate pathways that modulate mRNA translation. 2 The HIV-PIs were designed to specifically target the HIV protease. These safe and orally available molecules have been successfully used for more than 2 decades to decrease viral loads in infected patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation